2014
DOI: 10.1016/j.sbspro.2014.09.164
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Quality of Work Life and Career Advancement among Iranian Academics

Abstract: Background and aims : Career advancement can lead to productivity and success of educational canters and universities. Academic employees have a significant role in the community education and social development. Success in universities depends on academic employee's career advancement and quality of workplace. Quality of work life (QWL) views the organizational environment in accordance with employees' needs (health and safety, economic and family, social, esteem, actualization, knowledge and aesthetic). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
2
22
0
2
Order By: Relevance
“…), determinants of the growth, decline and competitiveness of organisations [61]; and (ii) as a set of non-economic factors, as a subject of research in the quality of academic life of students (QAL) (satisfaction with services, emotions felt in campus, etc. ), e.g., [62][63][64][65][66][67][68], or as a factor for assessing quality of work life (needs for satisfaction in a physical and emotional line) (QWL) [69][70][71][72][73].…”
Section: Sustainable Development Practices and Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…), determinants of the growth, decline and competitiveness of organisations [61]; and (ii) as a set of non-economic factors, as a subject of research in the quality of academic life of students (QAL) (satisfaction with services, emotions felt in campus, etc. ), e.g., [62][63][64][65][66][67][68], or as a factor for assessing quality of work life (needs for satisfaction in a physical and emotional line) (QWL) [69][70][71][72][73].…”
Section: Sustainable Development Practices and Quality Of Lifementioning
confidence: 99%
“…Recent years have witnessed an exponential increase in the number of studies on QoL in educational environments in relation to the different individuals and groups therein [63,67,68,[77][78][79], more specifically in the areas of students' QAL, e.g., [64][65][66][67][68] and the QWL of teachers and researchers [70,71]. QAL can be assessed in terms of feelings of global satisfaction with the student's experience of life at university [80].…”
Section: Sustainable Development Practices and Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…The evidences signify that improving both, either QoWL or diseases risk level will potentially beneficial either for staffs or the institution (Acheampong et al, 2016;Hatam et al, 2014;Kolbe-Alexander et al, 2008;Kuriyama et al, 2004;Parsa et al, 2014). However, this study suggested that improving QoWL may not directly improve diseseas risk level and oppositely.…”
Section: Discussionmentioning
confidence: 71%
“…Quality of work life questionnaire developed by Sergi et al 2001 (Sirgy, Efraty, Siegel, & Lee, 2001). This questionnaire was translated to Persian language by Parsa et al in 2014(Parsa, Idris, Samah, Wahat, & Parsa, 2014. The reliability of this scale is confirmed by alpha Cronbach equal to 0.81 and its validity was estimated by content analysis.…”
Section: Methodsmentioning
confidence: 97%